Environmental risk due to arsenic and boron in the watersheds Sama y Locumba from Perú - Dante Morales Cabrera; Edgardo Avendaño Cáceres; Daniel Zevallos Ramos; Julio Fernández Prado; Zoila Mendoza Rodas (Centro Provincial de Información de Ciencias Médicas, 2018)
A study was carried out to estimate the relative sustainable environmental risk with total concentrations of arsenic and boron in superficial waters of the watersheds Sama and Locumba, inTacna,Peru, through samplings of non probabilistic type by convenience in reference sites, during the months of August and November of 2016, as well as April and June, 2017.  It was obtained that the arsenic values in the respective months were 0,0731; 0,29835; 0,287 and 0,711 mg.L-1, which overcame the permissible maximum limit (0,01 mg.L-1); this unfulfillment was similar as for the boron, because concentrations of 8,681 and 4,148 mg.L-1 were found, but the established maximum value is 2,4 mg.L-1.  Concentrations determined per months revealed statistically significant differences (p≤0,05).  It was concluded that the superficial waters as natural resource were not sustainable and they represented an environmental risk and for the human health.